Pioglitazone versus Rosiglitazone: Effects on Lipids, Lipoproteins, and Apolipoproteins in Head-to-Head Randomized Clinical Studies - Mark A. Deeg; Meng H. Tan (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) play an important role in regulating both glucose and lipid metabolism. Agonists for both PPAR𝛾 and PPAR𝛾 have been used to treat dyslipidemia and hyperglycemia, respectively. In addition to affecting glucose metabolism, PPAR𝛾 agonists also regulate lipid metabolism. In this review, we will focus on the randomized clinical trials that directly compared the lipid effects of the thiazolidinedione class of PPAR𝛾 agonists, pioglitazone and rosiglitazone, head-to-head either as monotherapy or in combination with other lipid-altering or glucose-lowering agents